Colletotrichine B, a new sesquiterpenoid from Colletotrichum gloeosporioides GT-7, a fungal endophyte of Uncaria rhynchophylla. Issue 1 (2nd January 2019) - Chen, Xiao-Wei; Yang, Zhong-Duo; Li, Xiao-Fei; Sun, Jian-Hui; Yang, Li-Jun; Zhang, Xin-Guo
Abstract: One new compound, colletotrichine B (1 ), was produced by the fungal Colletotrichum gloeosporioides GT-7. The structure of1 was elucidated on the basis of spectroscopic analysis and X-ray crystallographic analysis. Monoamine oxidase (MAO), acetylcholinesterase (AChE) and phosphoinositide 3-kinase (PI3Kα) inhibitory activity of1 was also evaluated. Compound1 showed only AChE inhibiting activity with IC50 value of 38.0 ± 2.67 μg/mL. Abstract :